Cerium oxide nanoparticles with entrapped gadolinium for high T₁ relaxivity and ROS-scavenging purposes - Eriksson, Peter (2023)
Gadolinium chelates are employed worldwide today as clinical contrast agents for magnetic resonance imaging. Until now, the commonly used linear contrast agents based on the rare-earth element gadolinium have been considered safe and well-tolerated. Recently, concerns regarding this type of contrast agent have been reported, which is why there is an urgent need to develop the next generation of stable contrast agents with enhanced spin-lattice relaxation, as measured by improved T 1 relaxivity at lower doses. Here, we show that by the integration of gadolinium ions in cerium oxide nanoparticles, a stable crystalline 5 nm sized nanoparticulate system with a homogeneous gadolinium ion distribution is obtained. These cerium oxide nanoparticles with entrapped gadolinium deliver strong T 1 relaxivity per gadolinium ion (T 1 relaxivity, r 1 = 12.0 mM-1 s-1) with the potential to act as scavengers of reactive oxygen species (ROS). The presence of Ce3+ sites and oxygen vacancies at the surface plays a critical role in providing the antioxidant properties. The characterization of radial distribution of Ce3+ and Ce4+ oxidation states indicated a higher concentration of Ce3+ at the nanoparticle surfaces. Additionally, we investigated the ROS-scavenging capabilities of pure gadolinium-containing cerium oxide nanoparticles by bioluminescent imaging in vivo, where inhibitory effects on ROS activity are shown.